Overweight, obesity and risk of premenopausal breast cancer according to ethnicity: a systematic review and dose‐response meta‐analysis. Issue 8 (25th April 2013) - Amadou, A.; Ferrari, P.; Muwonge, R.; Moskal, A.; Biessy, C.; Romieu, I.; Hainaut, P.
Summary The association of overweight and obesity with premenopausal breast cancer remained unclear, ethnicity could play a role. A MEDLINE and PUBMED search of all studies on obesity and premenopausal breast cancer published from 2000 to 2010 was conducted. Dose‐response meta‐analysis was used to determine the risk of premenopausal breast cancer associated with different anthropometric measurements in different ethnic groups. For body mass index (BMI), each 5 kg m−2 increase was inversely associated with the risk of premenopausal breast cancer (RR = 0.95, 95% confidence interval [CI]: 0.94, 0.97). After stratification by ethnicity, the inverse association remained significant only among Africans (RR = 0.95, 95% CI: 0.91, 0.98) and Caucasians (RR = 0.93, 95% CI: 0.91, 0.95). In contrast, among Asian women, a significant positive association was observed. For waist‐to‐hip ratio (WHR), each 0.1 unit increase was positively associated with premenopausal breast cancer (RR = 1.08, 95% CI: 1.01, 1.16); the largest effect was detected in Asian women (RR = 1.19, 95% CI: 1.15, 1.24), while small effects of 5% and 6% were observed in African and Caucasian women, respectively. Our results suggest the importance of considering both fat distribution and ethnicity when studying premenopausal breast cancer.